THE ANALYSIS OF ENGLISH MID-TERM TEST ITEMS BASED ON THE CRITERIA OF A GOOD TEST AT THE FIRST SEMESTER OF THE EIGHTH GRADE STUDENTS OF MTS. MATHALIBUL HUDA MLONGGO IN THE ACADEMIC YEAR OF 2016/2017 - Nihayatus (Universitas Islam Nahdlatul Ulama Jepara)
This study was aimed at finding out the items quality of English Mid-Term Test at the First Semester of the Eight Grade Students of MTs. Mathalibul Huda Mlonggo in the Academic Year of 2016/2017 Based on the Criteria of a Good Test. The researcher analyzed the multiple-choice items with total 25 items which focused at (1) the face validity, (2) the content validity, (3) the reliability, (4) the difficulty level and (5) the discrimination power. The research method used was descriptive-qualitative method. The subject of this study was eighth grade students of MTs. Mathalibul Huda Mlonggo in the Academic Year of 2016/2017 class VIII E which has 40 students. The researcher used documentary study to collect the data. The finding showed that (1) the test has bad face validity since 92% or 23 (twenty three) items were error. There were only 8% or 2 (two) items categorized as appropriate items. (2) The test has good content validity since there were 88% or 22 (twenty two) items represent the basic competence and indicator as in the syllabus. (3) The test has high reliability since the reliability value of the items reached r11 = 0.691. Arikunto (2002:152) stated that reliability value which is between 0.61 ?? 0.80 has a high reliability. (4) The result of difficulty level analysis, the test was categorized into good test since 18 (eighteen) items (72%) were ideal items or having P around 0.62. There were 2 (two) items or 8% were founded as very easy items (P above 0.90). The rest 5 (five) items or 20% were categorized as very difficult items (P below 0.20). (5) The result of discrimination power analysis, the test has bad discrimination power since there were 20 (twenty) items (80%) were poor items category or having D 0.00 ?? 0.20 and 5 (five) items (20%) were satisfactory since they reached D 0.20 ?? 0.40. This means that the items needed to be revised. Keywords: Analysis, mid term test, good test criteria